EVALUATION OF MORPHOLOGICAL CHARACTERS AND ASSESMENT OF DNA CONTENT USING FLOWCYTOMETRY ANALYSIS IN REGENERANTS DWARF NAPIERGRASS FROM EMBRYOGENIC CALLI - Umami, Nafiatul (Pastura, 2014)
Callus is an excellent source for in vitro plant regeneration, but plants regenerated from callus sometimes show phenotypic and genotypic variation from the initial plants. In this study, there was no variations between regenerated plants and dwarf napiergrass as control. Research result on six morphological characters did not show differences between regenerated plants and control plants. There were not either significant differences of DNA content between control and regenerated plants. The method established by this research was a stable and efficient method that can be applied for supplying transformation materials using callus.
Keywords: Callus, morphological characteristic, dwarf napiergrass